NATURAL CONSERVATION AND IMPLEMENTATION VERP METHODS ANALYSIS AT TWA SANGIANG ISLAND, BANTEN - GILANG NUGRAHA, WILLY
This thesis is the final result of the research process on natural conservation for Small Island study objects in TWA Sangiang Island, Banten Province. The research process began from the awareness of the potential of Indonesia's natural beauty as a maritime country and the largest archipelago in the world as a diving activity, which saw that small island destinations turned out to have a lot of potential to be developed and have many obstacles to be able to develop as tourism destinations. Therefore, in achieving a tourism development goal, the use of a proper method is needed to improve the uniqueness of characteristics and quality of natural resource diversity that has its main potential. VERP was then selected as an analysis method used at research sites with consideration has been applied as a management guide in many national parks in the United States whose implementation needs to be tested in Indonesia. The Sangiang Island are then selected over 2 classifications as TWA and TWAL owned as well as the potential beauty of flora and fauna. In the process natural conservation then became the main key of this cycle of conservation of nature and also became a core value with the "privilege of identity" provided by the government. The natural conservation approach to Sangiang Island Natural Park ideally provides a more unique and different environment-based experience for tourists both so as to improve tourist visits and the quality of tourism development through educative elements. On the other hand, environmental damage due to disasters is also a factor in the need for a revitalization effort in restoring the privilege of the identity of the Natural Tourism Park to recover. The purpose of this research is to optimize natural resources as a potential attraction of natural tourism through zoning-based development through natural conservation, while the goal of this study is to identify various factors that are challenges, obstacles, current development and review what efforts can be done so as to maintain the sustainability of land and sea ecosystems and minimize the negative impacts that occur. The research design is carried out with mixed methods research design, where qualitative descriptive research as the main research method and quantitative research is added to complement the limitations and disadvantages of the existence of a research site with all its natural conditions. The collection of primary data from this study was conducted through field observations and interviews while quantitative research was conducted with the dissemination iv of questionnaires. The findings in the field are the high potential for disasters owned by Sangiang Island, the lack of infrastructure of tourism facilities and infrastructure that are suitable for tourists, limited capacity of tourists (carrying capacity) and the absence of accessibility for tourists to be able to reach all sides of the island. The conclusion of this study is that the inhibition of Natural Conservation-based development is a key in the restoration of TWA's identity as an asset to restore and revive the attractiveness of the tourism sector. The recommendation that needs to be done from this research is that there is a need for a physical and non-physical tourism development strategy to facilitate tourists and facilitate the management of the tourist area of TWA Sangiang Island to improve the quality of destination attraction through educative-based development to minimize the impact and improve environmental quality through the tourism sector.